FUNCTION JUKUNG FOR COMMUNITY ECONOMIC ACTIVITIES IN LOK BAINTAN VILLAGE, SUNGAI TABUK DISTRICT, BANJAR DISTRICT - Herlina Herlina; Mutiani Mutiani; Jumriani Jumriani (Indonesian Journal of Science Education and Applied Science, 2024)
Jukung is the name for traditional transportation from the Banjar tribe in South Kalimantan. In its current development, the use of jukung is starting to fade, due to the impact of globalization and technological advances in the land transportation sector which has resulted in a decline in interest in the use of traditional means of transportation such as jukung, which is now difficult to compete with more modern land vehicles. Despite this, the majority of Banjar people, especially those living in Lok Baintan Village whose homes are close to the river, still have a significant dependence on the water transportation system to carry out their economic activities. Jukung is used by the community as a means of transportation at the Floating Market. This floating market is very unique because the traders use jukung as selling stalls. This research aims to determine the function of Jukung for community economic activities in Lok Baintan Village, Sungai Tabuk District, Banjar Regency. This research is a type of qualitative research, which is carried out by collecting data, generally researchers can obtain descriptive data or documentation obtained from observation activities. The data collection techniques applied were observation, interviews and documentation. Research results show that jukungs are very functional for the community, namely that they can transport plantation agricultural products from rice fields and can be used as stalls for selling on floating markets. Then the jukung also functions to catch fish in the river and provide services for people who want to ride the jukung.Keyword: Function, jukung, economic activity. Jukung merupakan sebutan untuk alat transportasi tradisional suku Banjar di Kalimantan Selatan. Dalam perkembangannya saat ini, penggunaan jukung mulai memudar, dikarenakan adanya dampak globalisasi dan kemajuan teknologi di bidang transportasi darat yang mengakibatkan menurunnya minat penggunaan alat transportasi tradisional seperti jukung yang saat ini sudah sulit bersaing dengan kendaraan darat yang lebih modern. Meskipun demikian, sebagian besar masyarakat Banjar, khususnya yang tinggal di Desa Lok Baintan yang tempat tinggalnya dekat dengan sungai, masih memiliki ketergantungan yang cukup besar terhadap sistem transportasi air untuk menjalankan kegiatan ekonominya. Jukung digunakan oleh masyarakat sebagai alat transportasi di Pasar Terapung. Pasar terapung ini sangat unik karena para pedagangnya menggunakan jukung sebagai lapak berjualan. Penelitian ini bertujuan untuk mengetahui fungsi Jukung bagi kegiatan ekonomi masyarakat di Desa Lok Baintan, Kecamatan Sungai Tabuk, Kabupaten Banjar. Penelitian ini merupakan jenis penelitian kualitatif, yang dilakukan dengan cara mengumpulkan data, pada umumnya peneliti dapat memperoleh data deskriptif atau dokumentasi yang diperoleh dari kegiatan observasi. Teknik pengumpulan data yang diterapkan adalah observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa jukung sangat berfungsi bagi masyarakat, yaitu dapat mengangkut hasil pertanian perkebunan dari persawahan dan dapat dijadikan lapak untuk berjualan di pasar terapung. Kemudian jukung juga berfungsi untuk menangkap ikan di sungai dan memberikan pelayanan bagi masyarakat yang ingin menaiki jukung.Kata kunci: Fungsi, jukung, kegiatan ekonomi.